Volatility spillovers of Crude Palm Oil, Crude Oil, Coal, Exchange Rates and Indonesian Stock Market 2013-2023 - Savitri Agung Setiahutami; Dony Abdul Chalid (Green Publisher Indonesia, 2024)
This research is meant to analyze the Volatility spillover between the energy commodity market future (Crude Oil, Coal, and Palm Oil) with the Indonesian JKSE stock market and IDR-USD exchange rate. The data used is daily data taken from May 2013 until September 2023 by BEKK Diagonal Model. This research found that there were different patterns in asset pairs in relation to pre-pandemic and pandemic. Crude oil and palm oil had a positive relationship before pandemic and during the pandemic coal and the exchange rate had a positive relationship. Meanwhile, after the COVID-19 pandemic, no covolatility spillover was found. An increase in covolatility spillover from exchange rate asset pairs was found during the pandemic. This research also shows the potential for portfolio diversification for each asset pair through optimal portfolio weights. Understanding volatility movements and interdependencies in commodity futures, stock markets, and exchange rates is important for proper investment management, and this research can help investors make appropriate decisions.